Fluid load support does not explain tribological performance of PVA hydrogels. (February 2019) - Porte, Elze; Cann, Philippa; Masen, Marc
Abstract: The application of hydrogels as articular cartilage (AC) repair or replacement materials is limited by poor tribological behaviour, as it does not match that of native AC. In cartilage, the pressurisation of the interstitial fluid is thought to be crucial for the low friction as the load is shared between the solid and liquid phase of the material. This fluid load support theory is also often applied to hydrogels. However, this theory has not been validated as no experimental evidence directly relates the pressurisation of the interstitial fluid to the frictional response of hydrogels. This lack of understanding about the governing tribological mechanisms in hydrogels limits their optimised design. Therefore, this paper aims to provide a direct measure for fluid load support in hydrogels under physiologically relevant sliding conditions. A photoelastic method was developed to simultaneously measure the load on the solid phase of the hydrogel and its friction coefficient and thus directly relate friction and fluid load support. The results showed a clear distinction in frictional behaviour between the different test conditions, but results from photoelastic images and stress-relaxation experiments indicated that fluid load support is an unlikely explanation for the frictional response of the hydrogels. A more appropriate explanation, we hypothesized, is a non-replenished lubricant mechanism. This work has important implications for the tribology of cartilage and hydrogels as it shows that the existing theories do not adequately describe the tribological behaviour of hydrogels. The developed insights can be used to optimise the tribological performance of hydrogels as articular cartilage implants. Graphical abstract: Highlights: Provides direct evidence for fluid load support using photoelastic measurements. Frictional behaviour of hydrogels does not rely solely on fluid load support. Test configurations are essential to consider as part of tribological analysis. Lubricant replenishment hypothesized as explanation for tribological behaviour.